Coriophagus chaudhuri sp. n. (Strepsiptera: Halictophagidae: Coriophaginae): a male strepsipteran from Jharkhand, India with a tentative phylogeny and world key to known males - Hui, Poulami; Mukherjee, Bindarika; Hazra, Niladri (Zootaxa, 2023)
A new species of the genus Coriophagus Kinzelbach is described from the state of Jharkhand, India raising two in number from India. The new species, Coriophagus chaudhuri differs from other members of the genus in wing venation with base of R3 touching the subapex of R4, and flattened, oval-shaped foretarsomere I. The DNA barcoding of the new species has also been attempted here. An attempt is made to hypothesise the possible phylogenetic relationship of the males of the genus. A world key to known males of the genus is provided.